Follow that botanical: Challenges and recommendations for assessing absorption, distribution, metabolism and excretion of botanical dietary supplements. (November 2018) - Waidyanatha, Suramya; Ryan, Kristen; Roe, Amy L.; Jia, Wei; Paine, Mary F.; Ferguson, Stephen; Gurley, Bill J.; Welch, Kevin; Chow, Moses S.S.; Devito, Michael; Rider, Cynthia
Abstract: Botanical dietary supplements are complex mixtures containing one or more botanical ingredient(s), each containing numerous constituents potentially responsible for its purported biological activity. Absorption, distribution, metabolism, and excretion (ADME) data are critical to understand the safety of botanical dietary supplements, including their potential for pharmacokinetic botanical-drug or botanical-botanical interactions. However, ADME data for botanical dietary supplements are rarely available and frequently inadequate to characterize their fate in vivo . Based on an assessment of the current status of botanical dietary supplements ADME research, the following key areas are identified that require robust data for human safety assessment: 1) phytochemical characterization including contaminant analysis and botanical authentication; 2) in vitro and/or in vivo data for identifying potential botanical-botanical or botanical-drug interactions and active/marker constituents; 3) robust ADME study design to include systemic exposure data on active/marker constituents using traditional or novel analytical chemistry and statistical approaches such as poly-pharmacokinetics; and 4) investigation of human relevance. A case study with Ginkgo biloba extract is used to highlight the challenges and proposed approaches in using ADME data for human safety assessment of botanical dietary supplements. Highlights: ADME data are critical to understand botanical dietary supplement (BDS) safety. Challenges for characterizing ADME of BDS are highlighted. Ginkgo biloba was used as a case study to demonstrate the utility of ADME data. Approaches to characterize ADME of BDS are presented.